Exome sequencing of Familial Hypercholesterolemia patients: unique alterations in cholesterol related genes analysis - Alves, A.C. (2013)
Acknowledgements: Ana CatarinaAlves was funded by FCT SFRH / BD / 27990 / 2006 ; project grant FCT_PTDC/SAU-GMG/101874/2008